2016
DOI: 10.3390/ijms17071033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobial Denture Base Resin on Multi-Species Biofilm Formation

Abstract: Our aims of the research were to study the antimicrobial effect of dimethylaminododecyl methacrylate (DMADDM) modified denture base resin on multi-species biofilms and the biocompatibility of this modified dental material. Candida albicans (C. albicans), Streptococcus mutans (S. mutans), Streptococcus sanguinis (S. sanguinis), as well as Actinomyces naeslundii (A. naeslundii) were used for biofilm formation on denture base resin. Colony forming unit (CFU) counts, microbial viability staining, and 2,3-bis(2-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 48 publications
2
37
0
4
Order By: Relevance
“…Several other experimental antimicrobial denture materials have been developed, including a denture base resin containing dimethylaminododecyl methacrylate (DMADDM) (23). DMADDM is a quaternary ammonium salt (QAS) that can be copolymerized with acrylic denture base resin.…”
Section: Figmentioning
confidence: 99%
“…Several other experimental antimicrobial denture materials have been developed, including a denture base resin containing dimethylaminododecyl methacrylate (DMADDM) (23). DMADDM is a quaternary ammonium salt (QAS) that can be copolymerized with acrylic denture base resin.…”
Section: Figmentioning
confidence: 99%
“…Quaternary ammonium salts (QASs) can incorporate into many dental materials to combat oral bacterial species (Imazato, 2009;Cheng et al, 2017) by damaging the cell membrane (Beyth et al, 2006). A novel quaternary ammonium monomer, dimethylaminododecyl methacrylate (DMADDM) was proved to be a potential anti-caries dental material due to its long-lasting and remarkable antibacterial effects and well biocompatibility in vitro and in vivo (Cheng et al, 2013;Mei et al, 2013;Wang et al, 2016;Zhang et al, 2016). We identified that lethal concentration of DMADDM can induce the formation of S. mutans persisters by decreasing the metabolism for the first time (Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The effort in future studies should be directed to the elaboration of appropriate models of multi-species biofilms. As recent advances in this direction, model communities of multi-species biofilms relevant to dental medicine should be mentioned [35,36]. We expect that further work in this direction will provide novel laboratory models useful for the tests of anti-fouling substances.…”
mentioning
confidence: 99%